Adulticide Efficacy of Artemisia vulgaris L. against Aedes aegypti L. - Ninditya, Vika Ichsania; Purwati, Endah; Utami, Ajeng Tyas; Marwaningtyaz, Aprillyani Sofa; Fairuz, Nadia Khairunnisa; Hamid, Penny Humaidah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2019)
Aedes aegypti is the vector of various arthropod-borne diseases such as dengue fever, chikungunya and currently, zika. This study aimed to evaluate Artemisia vulgarisas other adulticides for controlling Ae. aegypti. Indonesian ministry of health hasbeen reported that more than 70.000 dengue fever human cases have occurred in 2015 covering 34 provinces which mean that dengue fever has spread now into all national territories. Eradication of Aedes still largely depends on insecticides, which is the most cost-effective strategy, and often inefficient due to resistance development in exposed Aedes population This study was designed to use of Centers for Disease Control and Prevention (CDC) bioassay standard. CDC bottles were coated with the ethanolic solution of extract with a concentration of 10, 50, 100, 500, 1000, 5000, 10000, 50000, and 100000 g per bottle. F0 mosquitoes were used for all experiments. Death and surviving mosquitoes were evaluated based on CDC standard assay. The test was performed with 10-25 adult mosquitoes every bottle and each concentration was repeated in triplicates. The results showed that LC50 and LC90 were 5790 g and 52110 g respectively after 120 minutes exposure to the extract. There was no mortality in ethanol control group. A. vulgaris significantly (P < 0.05) have adulticidal activity against Ae. aegypti. However, A. vulgaris have been reported to have larvacidal activity against Ae. Aegypti. These results indicated clearly that A. Vulgaris might act as the candidate of bioinsecticides for controlling Ae. aegypti. Keywords: Aedes aegypti, Artemisia vulgaris, adulticide,bio insecticide.